Utilização da cinza da casca do arroz no tratamento do teor de óleos e graxas de uma solução sintética de contaminante - Silva, Mariane Pimentel Felix da (Universidade Federal Rural do Semi-Árido, 2018)
The oil sector is constantly innovating its technological processes, however there are still some troubling problems. An example of this refers to the water produced, which is understood as all the water coming from the productive process of the oil, comes from the extraction or from other stages. One of the problems with regard to water produced is the difficulty of degradation of all the present compounds to an adequate level that allows the reuse or disposal of this water in the standards previously established by the environmental agencies. This problem has encouraged researchers to direct efforts to find alternatives capable of efficiently removing oils and greases, one of the main contaminants present in the water produced, at a lower cost compared to other technologies already used for the treatment of PA. Adsorption processes have a great potential for the removal of contaminants due to the ease of operation and simplicity in the design of the facilities, as well as low operating and maintenance costs compared to traditional water treatment methods. In this work, Rice Bark Ash (CCA) was used as adsorbent material in the removal of oils and greases from a synthetic solution through the adsorption process. The CCA was characterized from FRX analysis. The synthetic control solution was considered as the contaminant at 100% concentration. This solution was tested and, thus, its stability confirmed for the accomplishment of the analyzes. A control calibration curve was prepared in order to have a reliable parameter for the work calculations. Several samples were prepared and subjected to adsorption tests, which resulted in a removal of up to 98% contaminants. With the results of the adsorption test, a Factor Mapping was performed that confirmed the efficiency of the CCA as an adsorbent material. In this way, the CCA is an excellent adsorbent, with high percentages of oil and grease removal.
Monografia
Keywords: Cinza da casca do arroz; Adsorção; Adsorvente; Óleos e graxas; Remoção; Rice husk ash; Adsorption; Adsorbent; Oils and greases; Removal; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA